Low-cost potentiometric paper-based analytical device based on newly synthesized macrocyclic pyrido-pentapeptide derivatives as novel ionophores for point-of-care copper(ii) determination. Issue 44 (18th August 2021) - Kamel, Ayman H.; Amr, Abd El-Galil E.; Almehizia, Abdulrahman A.; Elsayed, Elsayed A.; Moustafa, Gaber O.
Abstract : A simple, cost-effective, portable and disposable paper-based analytical device is designed and fabricated for copper(ii ) determination. Abstract : A simple, cost-effective, portable and disposable paper-based analytical device is designed and fabricated for copper(ii ) determination. All solid-state ion-selective electrodes (ISEs) for copper and a Ag/AgCl reference electrode were constructed and optimized on the paper substrate. The copper electrodes were built using carbon nano-tube ink as a conductive substrate and an ion-to electron transducer. A suitable polymeric membrane is drop-cast on the surface of the conductive carbon ink window. The copper-sensing membrane is based on newly synthesized macrocyclic pyrido-pentapeptide derivatives as novel ionophores for copper detection. Under the optimized conditions, the presented all-solid-state paper-based Cu 2+ -ISEs showed a Nernstian response toward Cu 2+ ions in 30 mM MES buffer, pH 7.0 over the linear range of 5.0 × 10 −7 –1.0 × 10 −3 M with a limit of detection of 8.0 × 10 −8 M. The copper-based sensors exhibited rapid detection of Cu 2+ ions with a short response time (<10 s). The selectivity pattern of these new ionophores towards Cu 2+ ions over many common mono-, di- and trivalent cations was evaluated using the modified separate solution method (MSSM). The presented paper-based analytical device exhibited good intra-day and inter day precision. The presented tool was successfully applied for trace Cu 2+ detection in real samples of serum and whole blood collected from different children with autism spectrum disorder. The data obtained by the proposed potentiometric method were compared with those obtained by the inductively-coupled plasma (ICP) as a reference method. The presented copper paper-based analytical-device can be considered as an attractive tool for point-of-care copper determination because of its affordability, vast availability, and self-pumping ability, particularly when combined with potentiometric detection.